PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS PENEMUAN TERBIMBING BERBANTUAN GEOGEBRA PADA MATERI BANGUN RUANG SISI DATAR - Eka Setiawati; Dewi Risalah; Dwi Oktaviana (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
This study aims to produce student worksheets based on geogebra-assisted guided discovery on the material of flat-sided shapes that are valid, practical, and effective. This research is a research on the development of Dick and Carry with 5 stages, namely the stages of Analysis, Design, Development, Implementation, and Evaluation.Valid products are seen from the results of expert validation, practical products are seen from the results of the questionnaire, while effective products are seen from the results of trials. The results of the validation of the experts obtained that the material aspect was declared very valid with a result of 90.59%, while the media aspect was declared very valid with a result of 98.00%. The results of the teacher response questionnaire obtained results of 90.59%, while the results of the student response questionnaires were 93.37% with very practical criteria. The trial results obtained results of 80% with effective criteria where there were 8 students who passed and 2 students who did not complete the minimum passing standard determined by the school was greater than or equal to 70 for mathematics subjects, It can be concluded that geogebra-assisted discovery-based student worksheets are used with very valid criteria, very practical and effective.